Real-time microfluidic recombinase polymerase amplification for the toxin B gene of Clostridium difficile on a SlipChip platform. Issue 1 (5th November 2014) - Tsaloglou, M.-N.; Watson, R. J.; Rushworth, C. M.; Zhao, Y.; Niu, X.; Sutton, J. M.; Morgan, H.
Abstract : A SlipChip platform with six parallel 500 nL reaction chambers was fabricated using rapid prototyping in acrylic. We demonstrated real-time RPA with 1 fg (1000 copies) of DNA. Abstract : Clostridium difficile is one of the key bacterial pathogens that cause infectious diarrhoea both in the developed and developing world. Isothermal nucleic acid amplification methods are increasingly used for identification of toxinogenic infection by clinical labs. For this purpose, we developed a low-cost microfluidic platform based on the SlipChip concept and implemented real-time isothermal recombinase polymerase amplification (RPA). The on-chip RPA assay targets the Clostridium difficile toxin B gene ( tcdB ) coding for toxin B, one of the proteins responsible for bacterial toxicity. The device was fabricated in clear acrylic using rapid prototyping methods. It has six replicate 500 nL reaction wells as well as two sets of 500 nL control wells. The reaction can be monitored in real-time using exonuclease fluorescent probes with an initial sample volume of as little as 6.4 μL. We demonstrated a limit of detection of 1000 DNA copies, corresponding to 1 fg, at a time-to-result of <20 minutes. This miniaturised platform for pathogen detection has potential for use in resource-limited environments or at the point-of-care because of its ease of use and low cost, particularly if combined with preserved reagents.